Assessment of the Effects of Zoledronic Acid Therapy on Bone Metabolic Indicators in Hormone-Resistant Prostate Cancer Patients with Bone Metastatasis. (17th April 2011) - Demirtas, Abdullah; Sahin, Nurettin; Caniklioglu, Mehmet; Kula, Mustafa; Ekmekcioglu, Oguz; Tatlisen, Atila
Abstract : Purpose . Assessment of effects of zoledronic acid therapy on bone metabolic indicators in hormone-resistant prostate cancer patients with bone metastasis. Material and Methods . Hormone-resistant prostate cancer patients who were identified to have metastases in their bone scintigraphy were taken to trial group. Before administration of zoledronic acid, routine tests for serum calcium, total alkalen phosphates were studied. Sample sera for bone metabolic indicators BALP, PINP, and ICTP were collected. Bone pain was assessed via visual analogue scale and performance via Karnofsky performance scale. Four mg zoledronic acid was administered intravenously once a month. Results . When serum levels of bone forming indicators PINP; BALP were compared before and after therapy, there were insignificant decreases (P = .33, P = .21, resp.). Serum levels of bone destruction indicator ICTP was compared, and there was a significant decrease after zoledronic acid therapy (P = .04 ). When performances of the patients were compared during therapy period, performances decreased significantly due to progress of illness (P = .01 ). All patients had ostalgia caused by bone metastases at various degrees. Significant decrease in pain scores was observed (P < .01 ). Conclusion . Zoledronic acid therapy decreased bone destruction and was effective in palliation of pain in patient with bone metastasis. Using bone metabolic indicators during followup of zoledronic acid therapy might be useful.